Identification Damage of Rail Bridge Components Using Drone - Rusman Prihatanto; Adya Aghastya; Wahyu Tamtomo Adi (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2023)
Every railway infrastructure must be inspected to determine its condition and function, including railroad bridge. The current inspection method is still carried out manually, namely by directly inspecting the components of the railway infrastructure, of course, this will make the inspection time long. Inspection of bridge components in locations that are difficult to reach can use tools such as Unmanned Aerial vehicles (UAV) or Drones. This study aims at bridge components, damaged bridge components and the type of damage that occurs on Welded Through Truss (WTT) bridges. Video results obtained from drones were analyzed based on PM 31/2011 and PM 32/2011. The results of the analysis found that the damage that occurred was on the stringer, floor beam and top lateral bracing with the type of damage, namely corrosion/rust that occurred in all spans of the bridge. The underside of the bridge is still in good condition.